Fire Ants (Solenopsis spp.) and Their Natural Enemies in Southern South America - Juan Briano; Luis Calcaterra; Laura Varone (Psyche: A Journal of Entomology)
We review the fire ant research conducted by the ARS-South American Biological Control Laboratory (SABCL) since 1987 to find a complex of natural enemies in southern South America and evaluate their specificity and suitability for field release as self-sustaining biological control agents. We also include those studies conducted by the ARS-Center for Medical, Agriculture, and Veterinary Entomology in the United States with the SABCL collaboration. Ecological and biological information is reported on local fire ants and their microsporidia, nematodes, viruses, phorid flies, eucharitid wasps, strepsiptera, and parasitic ants. Their biology, abundance, distribution, detrimental effect, field persistence, specificity, and phenology are discussed. We conclude that the objectives of the ARS program in South America are being achieved and that the pioneering studies have served to encourage further investigations in the United States and other countries and advanced the implementation of biological control programs to decrease imported fire ant densities and damage. Still, several promising organisms should be further investigated for eventual field release in the near future.